Analysis of Water Quality of the Senibung River in the Oil Palm Plantation PT Telen East Kutai - Suwadi; Nataniel Tandirogang; Adi Susanto; Rudito; Edy Wibowo Kurniawan (Jurusan Pertanian Politeknik Pertanian Negeri Samarinda Kampus Sei Keledang Jalan Samratulangi, Kotak Pos 192 Samarinda 75123, 2025)
This study aims to analyze the water quality of the Senibung River flowing through the oil palm plantation of PT Telen, East Kutai. This analysis is very important to ensure that the water used as domestic water and the water used in palm oil processing is in good condition and not contaminated. The methods used are STORET and biological analysis with plankton abundance as an indicator of water quality. Sampling was conducted at the upstream (inlet) and downstream (outlet) sections of the river in March, June, September, and December 2024. The results indicate that the water quality is classified as good; however, several parameters such as TDS, BOD, nitrite, and ammonia exceed the threshold of water quality standards. The plankton diversity index in the downstream section is higher than in the upstream section, with values of H’ 1.47 and 1.17, respectively. Water discharge shows a significant positive relationship with TSS, BOD, COD, and the H' index, with the H' index having the strongest influence (R² = 0.711). The conclusion of this study is that the water quality in the downstream section is better than in the upstream section, and water discharge significantly affects water quality.